DAMPAK FAKTOR EKONOMI MAKRO DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Dewantara, Satria; Al Muizzuddin Fazaalloh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The aim of this research is to assess the impact of macroeconomic factors, including the inflation rate and Gross Domestic Product (GDP), and performance indicators such as Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER), on the valuation of manufacturing companies during the period from 2018 to 2022. This study employs purposive sampling to select ten companies as samples, with specific criteria applied throughout the five-year observation period. Data is collected through non-participant observation, involving the analysis of financial reports from the chosen companies. Data analysis iscarried out using multiple linear regression analysis techniques. The research findings reveal the significant positive influence of Return on Equity (ROE) on company value, whereas other variables do not exhibit significant impacts. This underscores the critical role of Return on Equity (ROE) as a key factor affecting company valuation.